Differences in the nutritional status of infants Aged 7-12 mounts WHO receife and Thouse WHO do not recheife exclusive breastfeeding in perning village, jetis district Mojokerto regency - Mardiyana, Rina; Hawa, Siti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Breastfeeding for babies is an absolute right. Unexclusively breastfeeded babies are easier to get chronic disease like cancers, heart disease, hypertension, and diabetic when they are adult. Probability risk to get malnutrition and obesity is higher. Because of that, tihs research is aimed to know the 7 to 12 months babies nutrition state difference between exclusively and unexclusively breastfeeded in Perning Village Jetis Sub District Mojokerto District. Research method used is correlation analitic with cross sectional approachment. The population of this research are all the 7 to 12 months babies in Perning Village Jetis Sub District Mojokerto District as many as 36 babies. Using purposive sampling technique has gotten 30 samples that fulfilled inclusion and exclusion criterias. The result of this research shows that all of 7 to 12 months babies nutrition state exclusively breastfeeded are normal as many as 7 babies (100%) from 7 exclusively breastfeeded, and most of 7 to 12 months unexclusively breastfeeded are normal as many as 12 babies (52,2%) from 23 unexclusively breastfeeded babies. Analyzed techique used is Mann Whitney Test, it’s gotten α =0,787, it means α > 0,05 thus H0 diterima, it means that there is no 7 to 12 months babies nutrition state difference between exclusively and unexclusively breastfeeded in Perning Village Jetis Sub District Mojokerto District. Eventhough mother didn’t give exclusively breastfeeding to their babies, but they tried to fufill their babies needs like giving formula milk, additional food, bananas mixed.Keyword : Exclusively breastfeeded, unexclusively breastfeeded, 7 to 12 months babies, nutrition state